PENGARUH KREATIVITAS IKLAN, MOTIVASI PEMROSESAN, DAN INTERAKSI DI SOSIAL MEDIA TERHADAP NIAT PEMBELIAN PT GOJEK TOKOPEDIA TBK: The Effect of Creativity Ad, Motivation Process, and Interaction in Social Media towards Purchase Intention of PT Gojek Tokopedia Tbk - Buon, Josia Pranata; Efrata, Tommy Christian (Universitas Ciputra Surabaya, 2025)
There are a lot of companies recently transform to technological field, one of them is Gojek from PT Gojek Tokopedia Tbk. Purchase intention is one of the expected by every company. In order to achieve it, strategies in social media such as creative advertising and interaction have been done by a lot of companies. This research has the purpose to see creativity ad, motivation process, and interaction in social media have the effect on purchase intention. This research uses Likert scale of 1-10, with Indonesian population that have ever even seen Gojek advertisement in social media, have used Go-Food, and have interacted in Gojek social media. In this research, it obtains 200 respondents by distributing online through social media using a purposive sampling technique. Data that is obtained by the researcher is processed using SEM PLS tool in smartPLS v3.0 software. This research finds out that creativity ad affects on motivation process, then motivation process and interaction affect on purchase intention. Another finding shows that creativity ad does not affect on purchase intention. With the results of four hypotheses are accepted and two hypotheses are not accepted.